Utilization of the Google Meet and Quiziz Applications in the Assistance and Strengthening Process of Online Learning during the COVID-19 Pandemic - Atika Rahmah Nasution; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2021)
The current Covid-19 pandemic has an impact on all fields including education. One of them is basic education, which requires teachers for online learning. The research objective is to fulfill the thematic student study service task regarding the Prevention and Management of the Impact of Covid-19 in the field of education. At this time, all learning in Indonesia is being pursued online so that there is minimal interaction. Therefore, this study aims to determine the effectiveness of online learning that takes place precisely for students at Elementary School 1 Telukagung Indramayu, Indonesia. The sample of this study was 11 students of sixth grade who were selected using simple random sampling technique by considering the homogeneity of the population. The data collection instrument used a pretest - posttest which was made in the Quiziz application with the aim of making students more interested in its various features. Data analysis used descriptive statistics with computerized assistance. The results of this study indicate that online-based learning at Elementary School 1 Telukagung Indramayu, Indonesia tends to be effective and runs smoothly.